2007
DOI: 10.1248/jhs.53.137
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Toxicity of Vanadyl Sulphate in Male Rats

Abstract: The reproductive functions were evaluated by epididymal sperm counts, motility, fertility rate, reproductive organ weights, biochemistry and histological examination of testes in vanadyl sulphate treated adult male Wistar rats. Oral administration of vanadyl sulphate (100 mg/kg b.wt./day) for 60 days caused a decrease ( p < 0.05) in the weights of testes and accessory reproductive organs. Cauda epididymal sperm analysis exhibited a significant decline in the number ( p < 0.01) and motility ( p < 0.001). Atroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 29 publications
(20 reference statements)
2
12
0
Order By: Relevance
“…Therefore, it might be suggested that impaired spermatogenesis further contributes to the declined level of sialic acid in the testes of exposed rats. The results are in accordance with previous researchers who also reported similar decline in sialic acid in testis due to the antiandrogenic or antispermatogenic impact of the metals (Chinoy et al, 2005;Jain et al, 2007). The level of sialic acid was significantly improved in ammonium molybdate treated rats after 60 days of treatment withdrawal probably due to restoration of androgen level.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, it might be suggested that impaired spermatogenesis further contributes to the declined level of sialic acid in the testes of exposed rats. The results are in accordance with previous researchers who also reported similar decline in sialic acid in testis due to the antiandrogenic or antispermatogenic impact of the metals (Chinoy et al, 2005;Jain et al, 2007). The level of sialic acid was significantly improved in ammonium molybdate treated rats after 60 days of treatment withdrawal probably due to restoration of androgen level.…”
Section: Discussionsupporting
confidence: 92%
“…Considering the functional outcomes in other species with similar lesions, these findings suggest that GonaCon-treated EGS males were at least temporarily immunocontracepted. 3,8,13,15 For example, our findings are consistent with those in other animals, such as GonaCon-treated male white-tailed deer, in whom testes size was also reduced as a result of antiGnRH immunocontraception. 2,3 Male EGS normally undergo a semiannual cycle of testicular recrudescence and regression and occasionally skip entire breeding seasons.…”
Section: Discussionsupporting
confidence: 90%
“…In particular, decreased reproductive performance of male rats and mice (mated with naïve females), was reported following oral exposure to vanadyl sulfate or sodium metavanadate, respectively, for 8–9 weeks [10], [11]. Weight changes in male reproductive-associated organs were not observed in the current studies, however more comprehensive assessment of effects on spermatogenesis would be needed to confirm whether or not vanadium has an impact on male reproductive performance.…”
Section: Discussionmentioning
confidence: 53%
“…Several studies in the literature, have reported effects of vanadium on developmental and reproductive endpoints following oral exposure [7], [10], [11], [21]. In particular, decreased reproductive performance of male rats and mice (mated with naïve females), was reported following oral exposure to vanadyl sulfate or sodium metavanadate, respectively, for 8–9 weeks [10], [11].…”
Section: Discussionmentioning
confidence: 99%